1980
DOI: 10.1136/bmj.280.6213.526
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure after a beer-drinking binge.

Abstract: 526BRITISH MEDICAL JOURNAL 23 FEBRUARY 1980 0-060 (normal < 0-022), and malabsorption of radiocalcium. We concluded that the hypercalcaemia was resorptive although there was no radiological evidence of bone lesions. A saline diuresis was started using 7 1 of 0 9 ,' saline and 2 1 of 5 % dextrose over the next 24 hours. Despite maintenance of fluid balance and a urinary loss of 27-3 mmol (1092 mg) of calcium (normal < 9 mmol/day) plasma calcium and renal function remained unchanged (fig).Peritoneal dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Alcohol may induce direct muscle injury, rhabdomyolysis, myoglobinuria, and therefore acute tubular necrosis. [13][14][15] As shown in both the cases, with normal CK levels, the ethanol-induced ARF in this syndrome is caused by a mechanism different from rhabdomyolysis. However, there are reports showing a slight increase of CK after binge drinking that may reflect some degree of muscle damage but not enough to satisfactorily explain ARF.…”
Section: Discussionmentioning
confidence: 96%
“…Alcohol may induce direct muscle injury, rhabdomyolysis, myoglobinuria, and therefore acute tubular necrosis. [13][14][15] As shown in both the cases, with normal CK levels, the ethanol-induced ARF in this syndrome is caused by a mechanism different from rhabdomyolysis. However, there are reports showing a slight increase of CK after binge drinking that may reflect some degree of muscle damage but not enough to satisfactorily explain ARF.…”
Section: Discussionmentioning
confidence: 96%
“…The data presented by Ghose et al [1] suggest the presence, in the beer consumed by the reported subjects, of a noxious agent other than the alcohol itself. Perhaps, here as in North America, cobalt has been incorporated into the beer during its manufacture.…”
mentioning
confidence: 89%
“…The first cases were reported in 1955, 1957 and 1962 [2-4]. Thereafter articles comprising 5 or 6 cases have been published [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%